2019
DOI: 10.21053/ceo.2018.00906
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Simulators for Endoscopic Sinus and Skull Base Surgery: The Present and Future

Abstract: Endoscopic sinus and skull base surgeries are minimally invasive surgical techniques that reduce postoperative symptoms and complications and enhance patients’ quality of life. However, to ensure excellent surgical outcomes after such interventions, intimate familiarity with important landmarks and high-level endoscope manipulation skills are essential. Cadaver training is one possible option, but cadavers are expensive, scarce, and nonreusable and cadaver work requires specialized equipment and staff. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
(20 reference statements)
0
14
0
2
Order By: Relevance
“…We would like to address the article titled "Virtual reality simulators for endoscopic sinus and skull base surgery: the present and future" by Kim et al [1]. In the field of endoscopic sinus and skull base surgery (ESSBS), many virtual reality simulators (VRS) have been developed.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to address the article titled "Virtual reality simulators for endoscopic sinus and skull base surgery: the present and future" by Kim et al [1]. In the field of endoscopic sinus and skull base surgery (ESSBS), many virtual reality simulators (VRS) have been developed.…”
Section: To the Editormentioning
confidence: 99%
“…Kim et al [1] observed that most of ESBSS-VRS nowadays intend to provide haptic feedback. However, there are few data regarding the development and validation of haptic rendering.…”
Section: To the Editormentioning
confidence: 99%
“…Performance [ 8 - 10 ]. As various methods of AI analysis have been developed and refined, the practical scope of AI in the otorhinolaryngological field has been broadened (e.g., virtual reality technology [ 11 - 13 ]). Therefore, it is essential for otorhinolaryngologists to understand the capabilities and limitations of AI.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 As such, there is no replacement for an intimate familiarity with the important anatomic landmarks and relationships within the sinuses to have consistently safe and positive outcomes. 6…”
Section: Introductionmentioning
confidence: 99%
“…4,5 As such, there is no replacement for an intimate familiarity with the important anatomic landmarks and relationships within the sinuses to have consistently safe and positive outcomes. 6 In skull base centers around the world, those performing complex sinus surgery are taught a common dictum to stay below the maxillary roof as a landmark to avoid iatrogenic skull base injury. One of many anatomic relationships within the sinuses, this was described anecdotally for decades until a recent study by Harvey et al 7 showed this association to be accurate and reliable in an objective evaluation.…”
Section: Introductionmentioning
confidence: 99%